Aortic tortuosity is related to aortic phenotype in patients with bicuspid aortic valve: a CT scan study of 83 cases. (14th October 2021) - Wallet, T; Milleron, O; Eliahou, L; Paul, J F; Arnoult, F; Lansac, E; Raffoul, R; Pellenc, Q; Ou, P; Jondeau, G
Abstract: Background: Although the incidence of aortic dissection is higher in patients with bicuspid aortic valve (BAV) compared to tricuspid aortic valve (TAV), risk stratification remains unclear. Guidelines focus on ascending aorta diameters, regardless of the location, and do not take into account the morphology of the aorta. Aortic tortuosity (AT) is emerging as a novel biomarker associated with more severe aortopathy in patients with Marfan syndrome. AT has not been accuretely assessed in BAV. Our aim is to describe the relationship between AT and ascending aortic phenotype in patients with BAV. Methods: 83 patients (43±16 years, 19 women) diagnosed with BAV and without significant aortic valve disease nor prior aortic intervention were included. CT scans were retrospectively analysed with measurements of aortic diameters and aortic tortuosity. For 61 patients with abdominal images available, descending and total aortic length and tortuosity were measured. Results: In our cohort, 62 (75%) patients presented a typical BAV. Pathological aorta (Root and/or tubular Z-score >2) was found in 80 patients (96%) and 67 (81%) presented a tubular dilatation. The aortic phenotype, the maximal aortic diameters and aortic tortuosity index were similar in typical and atypical BAV. Total aortic tortuosity index was correlated to Z-score tubular diameter (r=0.31; p=0, 014) but not with Z-score Valsalva diameter (p=0, 55). In patients with tubular dilatation (Z score >2), total aortic tortuosity index was higher than in patient without tubular dilatation (2.01 vs 1.85; p=0, 015). Conclusion: Total aortic tortuosity is associated with tubular dilatation but not with root dilatation in BAV patients suggesting that tubular phenotype may be at higher risk of complication in BAV. Further studies evaluating the association between aortic tortuosity and clinical outcomes in BAV are needed. Funding Acknowledgement: Type of funding sources: None.